EMPLOYEE PERFORMANCE IN THE VUCA ERA: DETERMINANTS OF AGILE LEADERSHIP AND JOB SATISFACTION - Teguh Setiawan Wibowo; Rini Fatmawati; Sunday Ade Sitorus; Hartanto Hartanto; Didi Suhendi; SUNDAY ADE SITORUS (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research is motivated by the problem of a tendency to decrease employee performance. This study aims to identify and analyze the influence of agile leadership and employee job satisfaction in the VUCA era. This research method is descriptive with a quantitative approach. The sample in this study were 100 employees who were taken by random sampling. The instrument used in this study was a questionnaire distributed via the Google form. The instruments used have been tested for validity and reliability. The collected data was analyzed using the classical assumption test and multiple linear regression using the SPSS application. The results of this study explain 1) Agile leadership has a positive and significant effect on employee performance in the VUCA era, 2) Job satisfaction has a positive and significant effect on employee performance in the VUCA era, and 3) Agile leadership and job satisfaction have a positive and significant effect on performance employees in the VUCA era. The findings of this study indicate that if companies want to improve employee performance in the VUCA era, companies must improve agile leadership and job satisfaction.